Management of post‐inflammatory hyperpigmentation in skin of color: A short review. (21st March 2022) - Anvery, Noor; Christensen, Rachel E.; Dirr, McKenzie A.
Abstract: Post‐inflammatory hyperpigmentation (PIH) is a common cosmetic complaint affecting patient quality of life. PIH has been proven to disproportionately affect skin of color. While several treatment options exist, special consideration must be given when managing PIH in patients of color, as topical treatments and aesthetic procedures, such as chemical peels and lasers, may either exacerbate or prove ineffective against PIH.